Preparation and Characterisation of Thio-kaolinite Nanohybrid Materials for Heavy Metal Sorption from Wastewater - Struijk, Marijke (Université d'Ottawa / University of Ottawa, 2016)
Heavy metals are non-degradable and their persistence constitutes ecotoxicological ramifications. Their presence in wastewater is inhibitory to microbial digestion processes and can lead to biomagnification in the environment. Clay minerals have been widely studied as inexpensive sorbent materials of aqueous-phase contaminants. Particularly in the case of kaolinite, a non-swelling clay with a low cation-exchange capacity, chemically enhanced derivatives exposing its OH-rich interlayer space to interactions with its external environment are of exceptional interest. The objective of this study was to prepare a novel functionalised kaolinite with the aim of significantly improving its heavy-metal sorption capacity. Due to the robustness of sulfur-metal linkages, the compound 3,6-dithia-1,8-octanediol (HO(CH2)2S(CH2)2S(CH2)2OH) was grafted onto both urea- and DMSO precursors of two kaolinitic clays: the Source clay KGa-1b and a Portuguese clay sample collected from the Clays of Taveiro formation. All samples were characterised by X-ray diffraction and 13C nuclear magnetic resonance spectroscopy (NMR). Initial materials and final samples were also characterised by thermal gravimetric analysis and infrared spectroscopy. The results describe nanohybrid materials that are resistant to hydrolysis and exhibit different grafting fashions. Application as a heavy metal sorbent was tested in ZnCl2 solutions as well as in zinc-spiked raw wastewater. Zinc concentrations were analysed concomitant with other metal species by inductively coupled plasma – mass spectrometry, demonstrating variable sorption capacities of the different clay samples tested and a consistently greater zinc removal in the wastewater system compared to simple zinc solutions. Measured concentrations of concomitantly analysed metals reveals a potentially alarming release of certain heavy metal species from some clay samples as a result of zinc sorption.
Keywords: clay; kaolinite; intercalation; grafting; nanohybrid material; wastewater treatment; sorption; heavy metals; zinc; 3; 6-dithia-1; 8-octanediol; thio; chelation